1987
DOI: 10.1111/j.1365-2125.1987.tb03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory and respiratory effects of infused adenosine in conscious man.

Abstract: 1. The nucleoside, adenosine, was infused into six conscious healthy male subjects at rates up to 100 micrograms kg‐1 min‐1. 2. Compared with a control 0.9% saline infusion, adenosine in all subjects caused dose dependent increases in heart rate, skin temperature and minute ventilation with corresponding falls in PaCO2, estimated transcutaneously. 3. There were no changes in systemic blood pressure, airways resistance (measured by forced partial expiratory manoeuvres), or plasma catecholamines. At the top infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…We and others Torsell et al, 1985) have not observed any reflex tachycardia, which could be an advantage compared with agents such as sodium nitroprusside or prostacyclin (Sollevi, 1986;Bush et al, 1988). However, some workers have reported tachycardia in supine subjects (Fuller et al, 1987;Watt et al, 1987;Conradson et al, 1987) and with higher doses (0.14 mg kg-' min-) of adenosine (Sollevi, 1986). The differences may be related to posture, dose, or differences in individual sensitivity.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We and others Torsell et al, 1985) have not observed any reflex tachycardia, which could be an advantage compared with agents such as sodium nitroprusside or prostacyclin (Sollevi, 1986;Bush et al, 1988). However, some workers have reported tachycardia in supine subjects (Fuller et al, 1987;Watt et al, 1987;Conradson et al, 1987) and with higher doses (0.14 mg kg-' min-) of adenosine (Sollevi, 1986). The differences may be related to posture, dose, or differences in individual sensitivity.…”
Section: Resultsmentioning
confidence: 95%
“…Inspection of these data revealed significant changes only for Qp.eff ( Figure 2) and SVR (Figure 3) at the highest dose of adenosine. Since tachycardia has been reported during adenosine infusion (Sollevi, 1986;Fuller et al, 1987;, the heart rate data are also plotted (Figure 4) Time (min) Figure 4 Change in heart rate (HR) in beats min-'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…theophylline (Hedner et al, 1982;Eldridge et al, 1985). On the other hand, adenosine stimulates breathing in conscious, unanesthetised humans (Fuller et al, 1987;Griffith et al, 1997). The depressant effect of adenosine on breathing in vivo is more potent during the time period around birth and/or is also more severe in anesthetised animals (Herlenius et al, 2002).…”
Section: Ballanyi K Atp Channels In Brain Hypoxiamentioning
confidence: 99%
“…In contrast to these observations, it has been found that adenosine increases contractility of the isolated rabbit heart (33) and ventricular preparations from the guinea pig heart (32). Adenosine infusion was also found to increase the cardiac output in normal subjects and in patients with coronary disease (25,26,34). On the other hand, it has been shown that adenosine produced no inotropic effect in isolated guinea pig ventricles (35).…”
Section: Statistical Analyses Of Resultsmentioning
confidence: 98%